Pioneers of African Initiated Churches (AIC) as actors of development: A case of Paulos Matsea Mureri of the United African Apostolic Church (UAAC) and community development - Ranwedzi, Ndivhuwo Emmanuel; Nesamvuni, Azwihangwisi E.; van Niekerk, Johan (Technium Social Sciences Journal, 2022)
The role of Africans, those associated with African Initiated Churches (AIC), in spreading the gospel, which contributed to human development, has not been fully recognized even in the current political dispensation in South Africa. Most literature has given specific focus to the western missionaries and their approach to the gospel has been widely accepted as the way of the gospel. The establishment of AICs such as the United African Apostolic Church (UAAC) initiated by Matsea Paulos Mureri display an unignorable phenomenon in terms of the contribution he made as a gospel crusader and actor of development within and outside his community. Through the seed that Matsea Paulos Mureri planted, the church has grown to over a million members internationally. He comes from a generation that experienced the emergence of the Pentecostal movements which shaped the African Initiated Pentecostal Churches (AIPC) and they have survived a century of various marginalization. Unlike Evangelical and Pentecostal movements, their contribution to human development has been recognized through their contribution to education and health sectors. However, human development concept is much broader. In terms of Paulos story, important questions are asked in reflection of some of the challenges which continue to confront the AICs particularly in the area of succession. Like most of the AICs, the UAAC has not been spared from disputes and splits which have confronted most AICs since their inception. Some of the imperative questions asked is whether the leadership conflicts and disputes which surround the AIC’s are real leadership disputes or are polygamous conflicts which are disguised under church leadership battles. Secondly, a question is raised about the contestation of two opposing cultures i.e. the African unwritten law versus the western written law on the rights and privileges of adopted children in terms of succession. Although the two question may sum up the kind of legacy that Matsea Paulos Mureri left in his quest to be a gospel distributor, it does not erode his contribution to human development.